Numerical study of magnetized Powell–Eyring hybrid nanomaterial flow with variable heat transfer in the presence of artificial bacteria: Applications for tumor removal and cancer cell destruction - Tang, Tao-Qian; Rooman, Muhammad; Shah, Zahir; Khan, Saima; Vrinceanu, Narcisa; Alshehri, Ahmed; Racheriu, Mihaela (Frontiers in Materials, 2023)
The intention of the investigation is to determine the effectiveness of an external magnetic field on bacteria that are enclosed by thousands of magnetite nanoparticles. Variable thermal conductivity and Joule heating are used in the interstitial nanoliquid wherein an artificial bacteria swims in a biological cell. The unsteady motion of a Powell-Eyring fluid in two dimensions is considered. The porous stretching wall is used as a curved surface pattern. To convert the governing nonlinear PDEs into nonlinear ODEs, suitable transformations are exploited. The Homotopy analysis method (HAM) is utilized to resolve the semi analytical results of nonlinear ODEs. Plots are utilized to investigate the influence of significant parameters of velocity distribution, temperature profile, bacterial density field, nutrient concentration field, Skin friction, Nusselt number, and density of nutrient concentration number. Clinical disease has shown that dangerous tumours have reduced blood flow. This study concludes that augmenting the values of the unsteady parameters improves the blood velocity profile. The velocity profile declined for higher values of magnetite volume fraction, porosity parameter, and magnetic parameter. As the concentration of magnetite nanoparticles increases, so does the distribution of blood temperature. As a result, by immersing the magnetite nanoparticles, the physical characteristic of the blood can be improved. Furthermore, the current findings demonstrated that magnetic parameter and Eckert number play an important role in increasing heat transfer rate.